Embedded Model Control for UAV Quadrotor via Feedback Linearization. Issue 17 (2016) - Lotufo, M.A.; Colangelo, L.; Perez-Montenegro, C.; Novara, C.; Canuto, E.
Abstract: This study investigates the use of the feedback linearization approach as a novel way to design the internal model for Embedded Model Control (EMC). The feedback linearization allows to collect all the nonlinearities at command level. EMC, by means of a disturbance dynamics model, makes possible to estimate and then reject the non-linear terms through the control law. This idea is applied to the control of an Unmanned Aerial Vehicle: the Borea project quadrotor. Embedded Model Control methodology implies the design of an internal model (Embedded Model) coded into the control unit and running in parallel with the plant. The attitude reconstruction problem is faced by means of a state observer developed on purpose and fully integrated with the model. A two-modes control strategy is proposed in order to reject systematic sensor errors, thus enhancing the attitude estimation capability. Using a high-fidelity numerical simulator, the feasibility of the proposed control strategy was demonstrated. This indicates that a feedback linearization approach allows the extension of EMC techniques to non-linear systems control. What is more, the EMC was successfully applied to the control of the Borea quadrotor.